Development Of An Integrated Educational Guidance Donation Payment Application: A Study At A Vocational High School In Cimahi - Hilga Rizky Hilga Rizky Nugraha; Dadi Rosadi; Cahyo Hermanto; En Tay (Informatics Management, Engineering and Information System Journal, 2025)
The Educational Development Contribution is a levy imposed on students to assist educational institutions in enhancing the teaching and learning process within schools.  This contribution is a monthly school charge mandated for every active student.  The inadequate payment recording method may result in data loss and accountability challenges in report generation.  For example, at a vocational institution in Cimahi, the SPP payment system continues to depend on a manual method, wherein administrative personnel and the treasurer document payments utilising a ledger.  This scenario results in numerous errors and significantly prolongs the payment recording process.  The author utilises an Object-Oriented Analysis and Design (OOAD) methodology for this project.  The system will be designed as a web-based application coupled with the institution's website.  The author used PHP, CSS, the CodeIgniter framework, a MySQL database, and Visual Studio Code as the code editor to resolve challenges throughout system installation.  The employed system testing methodology is Black Box testing.  The method devised by the author facilitates the input of student data and the administration of Educational Development Contribution payments.